Atrial fibrillation screening on holter monitoring after percutaneous patent foramen ovale closure: a prospective study. (14th October 2021) - Leclercq, F; Odorico, X; Arquizan, C; Macia, J C; Lattuca, B; Schmutz, L; Roubille, F; Pages, L; Marin, G; Cayla, G; Akodad, M
Abstract: Background: An increased risk of new-onset atrial fibrillation (AF) after patent foramen ovale (PFO) closure was observed in randomized trials. However, systematic screening of AF was not performed in these studies. Purpose: We aimed to evaluate incidence of AF in patients undergoing percutaneous PFO closure with serial 24-hours ambulatory electrocardiogram (AECG) monitoring during a 6-months follow-up. Methods: All consecutive patients undergoing PFO closure for cryptogenic stroke or decompression sickness (DSC) were prospectively included in 2 centers. AF was defined as an irregular rhythm without discernible P waves lasting at least 30 seconds on 24-hours AECG performed at day 0, 1 month and 6-months follow-up. Primary endpoint was incidence of AF within the study period. Secondary endpoints evaluated clinical outcomes (hospitalization for cardiovascular causes, new stroke or bleeding) within 6-months follow-up. Results: Between February 2018 and March 2019, a total of 62 patients underwent PFO closure: 59 (95.2%) for cryptogenic stroke and 3 (4.8%) for DSC. In the overall population, 40 were male (64.5%) and the mean age was 48±9.5 years. An atrial septal aneurysm was present in 37 patients (64.9%). The PFO device mean size was 26±5.0 mm. After a mean follow-up of 33.3±12.2 weeks, new-onset AF occurred in 3 patients (4.8%), all within 1-month after closure and paroxysmal. While symptomatic ectopic atrial heart beats occurred in one fourth of patients, all AF episodes asymptomatic. Two patients (3.2%) required oral anticoagulant therapy according to CHA2DS2-VASc score. No adverse outcomes occurred. Age (RR 1.26 [0.98; 1.61] p=0.3), male sex (p=0.6) and device (p=1.0) were not associated with occurrence of AF but all patients with AF were men and received an Amplatzer device. Conclusion: Incidence of AF, evaluated with serial systematic 24-hours AECG during a 6-months follow-up after PFO closure, was relatively low (<5%). Always paroxysmal, AF always occurred within one month after the procedure and was not associated with adverse outcomes. Funding Acknowledgement: Type of funding sources: None.